Pinpointing the Mechanism of Magnetic Enhancement in Modern Soils Using High‐Resolution Magnetic Field Imaging. (1st March 2023) - Fu, Roger R.; Maher, Barbara A.; Nie, Junsheng; Gao, Peng; Berndt, Thomas; Folsom, Elizabeth; Cavanaugh, Timothy
Abstract: In well‐buffered modern soils, higher annual rainfall is associated with enhanced soil ferrimagnetic mineral content, especially of ultrafine particles that result in distinctive rock magnetic properties. Hence, paleosol magnetism has been widely used as a paleoprecipitation proxy. Identifying the dominant mechanism(s) of magnetic enhancement in a given sample is critical for reliable inference of paleoprecipitation. Here, we use high‐resolution magnetic field and electron microscopy to identify the grain‐scale setting and formation pathway of magnetic enhancement in two modern soils developed in higher (∼580 mm/y) and lower (∼190 mm/y) precipitation settings from the Qilianshan Range, China. We found that both soils contain 1–30 μm aeolian Fe‐oxide grains with indistinguishable rock magnetic properties, while the higher‐precipitation soil contains an additional population of ultrafine (<150 nm) magnetically distinct magnetite grains. We show that the in situ precipitation of these ultrafine particles, likely during wet‐dry cycling, is the only significant magnetic enhancement mechanism in this soil. These results demonstrate the potential of quantum diamond microscope magnetic microscopy to extract magnetic information from distinct, even intimately mixed, grain populations. This information can be used to evaluate the contribution of distinct enhancement mechanisms to the total magnetization. Plain Language Summary: Reconstructing how natural climate variations in the past influenced rainfall patterns is important for understanding how rainfall would respond to our current changing climate. The amount and properties of microscopic, magnetic minerals in soil can change due to variation in soil moisture; therefore, characterizing the magnetic properties of soils can aid in quantifying past rainfall. We use the quantum diamond microscope (QDM), a device that allows micrometer‐scale mapping of magnetic sources in rock and soil samples, to investigate the magnetic properties of two soils formed in low‐ and high‐rainfall environments. We find that, although both soils contain wind‐blown, magnetic dust, only the high‐rainfall soil contains an abundant, highly magnetic population of magnetite grains formed in soil pore spaces during repeated cycles of wetting and drying. These observations demonstrate the dominant pathway by which soil magnetism responds to rainfall and showcase the ability of QDM mapping to reliably identify the mechanism of magnetism modification in soils. Key Points: Both high and low precipitation soils contain aeolian grain population with indistinguishable magnetic properties High precipitation soil alone contains anhysteretic remanent magnetization‐susceptible, <150 nm magnetites inferred to be formed from wet‐dry cycling in pore spaces Magnetic field microscopy is able to quantify rock magnetic properties of intimately mixed grain populations and pinpoint their locations